Pengoptimalan Hasil Penjualan Kue Dengan Menggunakan Metode Simpleks - Damaris Lalang; Jeni Marianti Loban; Narita Yuri Adrianigsih; Junindasari Djenlau (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This research aims to maximize profits from selling cakes and find out the optimal number of each type of cake to be produced according to the limits available to Mrs. Farida Bako. The data collection technique was carried out by direct interviews with the respondent, namely Mrs. Farida Bako. The data analysis technique used is the simplex method in order to produce maximum profits by knowing the number of cake types produced. The research results show that maximizing and knowing the number of production results can maximize profits of IDR. 1,153,000